Analysis of Actor Networks in Forest Management as a Buffer for Water Resources in Archipelago Areas (Study on Sei Pulai Protected Forest Area, Riau Islands) - Imam Yudhi Prastya; Jamhur Poti (Iapa Proceedings Conference, 2018)
This study aims to analyze actor networks in the management of Protection Forest as the Pulai River. Pulai River Protected Forest is one of the protected forests on the bintan island of Riau Islands Province in addition to the protected forest of the cat hill, the mountain of galangal and the mountain of the deer. The protected forest of Pulai River is a buffer or provider of water reserves and also as a water catchment area for the Pulai River reservoir. The current level of damage to the protected forest of the river Pulai is very worrying. The damage is caused by illegal logging, conversion of forest areas to residential and community plantations and also the existence of oil palm plantations that enter protected forest areas. In this study qualitative descriptive approach with explanatory level will be used, to see patterns, meaning of actor objects, function, structure, institutionalization, rules of conduct, power relations and actor strategies, placing in-depth interviews as data collection cores. The author concludes that the network of actors in management in Forest Management as a Buffer for Water Resources in the Islands Region has not been formed. This is due to the lack of understanding and agreement that the forest issue is not only a matter of forest rehabilitation. Another thing is about the certainty of ownership rights over land which then has an impact on the fulfillment of the rights regarding the basic needs of the citizens who have been fulfilled. With the issuance of regulations relating to the settlement of land in forest areas, it is at least a new hope to address the core of the problem.